Protein based technologies to identify, study, and control intracellular processes - Bruce, Virginia Jane, author; McNaughton, Brian, advisor; Ross, Eric, committee member; Di Pietro, Santiago, committee member; Fisk, Nick, committee member (Colorado State University. Libraries, 2017)
Proteins are increasingly used as basic research tools and therapeutics. Their large size, complex structure, and functional group diversity, by virtue of amino acids, often permit recognition of surfaces that challenge small-molecules. Fundamentally, this thesis describes protein based solutions to identifying macromolecules that function inside mammalian cells, enabling visualization and the study of complex biological processes in cellular environments. It also describes the development of engineered polycationic cell-penetrating nanobodies that access the cytosol and thus possibly represent a general solution to intracellularly targeted biologics drug discovery. Collectively, the work described in this thesis reports on: (1) a prostate cancer cell-selective cell penetrating peptide, and its optimization; (2) cell-penetrating nanobodies that access the cytosol of mammalian cells; (3) the use of engineered protein assemblies for bioanalytical reagents and to visualize transcription and translation in mammalian cells, and; (4) a new protein reassembly-based technology to measure cytosolic residence of intracellularly delivered proteins. Technologies and methods described in this work advance the use of proteins in basic science and therapeutically-relevant environments.
Keywords: cellular delivery; proteins; cell penetrating peptides; resurfacing; protein engineering